Gabor wavelet and multiclass support vector machine for braille image classification - Agustina, Feri; Rachmawanto, Eko Hari; Putri, Ni Kadek Devi Adnyaswari; Saputro, Fakhri Rasyid; Lestiawan, Heru; Suprayogi, Suprayogi; Huda, Solichul (Journal of Soft Computing Exploration, 2024)
Braille is a letter designed for the visually impaired. As a family with normal vision who have a visually impaired child find it difficult to Teach their child how to learn and understand the process of learning from home. Learning braille requires good finger sensitivity and memory to memorize each letterform, making it difficult to learn.  With this study, braille letters can be detected from the image using the Gabor Wavelet method to extract braille images and combined with the Multiclass Support Vector Machine (Multiclass SVM) algorithm as a classification method for extracted braille images. Data testing was performed using a confusion matrix to determine the level of precision, accuracy, and recall. According to the results of tests performed on 910 braille data using confusion matrix, the highest recognition accuracy was 98,02%. The accuracy of these results is impacted by the parameters of the training process, the training data, and the test data used. This research has the opportunity to be developed in voice-based card recognition to help the visually impaired in the future research.